2021
DOI: 10.3389/fmed.2021.741407
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Classification Based on Attention Residual Feature Pyramid Network

Abstract: Clinically, red blood cell abnormalities are closely related to tumor diseases, red blood cell diseases, internal medicine, and other diseases. Red blood cell classification is the key to detecting red blood cell abnormalities. Traditional red blood cell classification is done manually by doctors, which requires a lot of manpower produces subjective results. This paper proposes an Attention-based Residual Feature Pyramid Network (ARFPN) to classify 14 types of red blood cells to assist the diagnosis of related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…, of stored RBCs, results in a change in the RBC lateral distribution, especially at high velocities ( Figures 2 , 4 ). Additionally, employing machine learning algorithms enabled us to characterize pathological RBC morphologies under constant flow, similar to previous studies in stasis ( Moon et al, 2021 ; Simionato et al, 2021 ; Song et al, 2021 ; Lamoureux et al, 2022 ). This allowed us to detect morphological changes, distinctive for a certain disease, such as the acanthocytes shown in Figure 2 , or treatment (HDF, Figure 3 ).…”
Section: Discussionmentioning
confidence: 67%
“…, of stored RBCs, results in a change in the RBC lateral distribution, especially at high velocities ( Figures 2 , 4 ). Additionally, employing machine learning algorithms enabled us to characterize pathological RBC morphologies under constant flow, similar to previous studies in stasis ( Moon et al, 2021 ; Simionato et al, 2021 ; Song et al, 2021 ; Lamoureux et al, 2022 ). This allowed us to detect morphological changes, distinctive for a certain disease, such as the acanthocytes shown in Figure 2 , or treatment (HDF, Figure 3 ).…”
Section: Discussionmentioning
confidence: 67%
“…Some previously developed machine-learning methods for the classification of RBC abnormalities have been limited by small or poor-quality data sets, 16 choice of nonstandard classification categories, 33 and limited clinical correlation. 17 , 18 Other approaches have shown good performance in larger or well-defined data sets, 17 , 20 and have often focused on individual cell classification without validation at the smear level or in the context of clinical care. Because human assessment of an individual morphology of a cell will be informed by morphologic heterogeneity across the entire smear, the clinical application of blood smear analysis involves consideration of the overall RBC population.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 13 , 14 These systems assist in creating semiquantitative grading but are not sufficiently calibrated for important RBC subtypes, such as schistocytes, 7 , 14 and the corresponding hardware may not be available in resource-limited settings. Research and development of additional tools have been hampered by poor reproducibility, 15 inadequately small image data sets, 16 limited clinical testing, 17 , 18 or narrow focus on a few morphologies. 19 Although some recent approaches have shown promise, 17 , 20 , 21 they have not been validated at the cell population level, at which clinical assessments are made, nor have they been shown to add value in clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we concluded that the RNA in the RBCs was stable and unaffected by the storage conditions and consistent with previous reports of human erythrocytes [ 30 , 31 ]. RBCs undergo denucleation during their maturation from blood stem cells before entering the peripheral blood [ 32 , 33 ]. It can also be speculated that the RNA in the RBCs is generated before denucleation.…”
Section: Discussionmentioning
confidence: 99%